Islamic corporate governance and sustainable financial growth - Raja, Rehan; Abdul Razak, Abdul Hadi; Adam Sa'ad, Auwal (Emerald Publishing Limited, 2025)
The former financial fiascos from Enron to slumps of capital markets dur- ing covid-19 pandemic are also measured as a failure of corporate govern- ance systems. However, the circumstances are different for Islamic financial institutes as they competently handle the rising risk and prove beneficial for their nominees during financial disasters. This highlights the Islamic finance offered services and products around the globe which are considered and proven themselves for delivering sustainable financial growth. The Islamic finance regulatory bodies such as the financial services board (IFSB) and the accounting auditing organization for islamic financial institutions (AAOIFI) established several governance standards (GSs) that open the way for Islamic finance institutions to develop vigorous Islamic corporate governance proce- dures. The AAOIFI and IFSB frameworks for Islamic corporate governance clarify that there must be a central Shariah board, supervisory council, inter- nal compliance, internal audit, and external independent audit to ensure the Shariah obedience of Islamic finance institutions. The AAOIFI and IFSB familiarized GSs support the establishing of Islamic corporate governance procedures that are rooted in Islamic principles, thus, when executed they deliver sustainable financial growth. Besides, Islamic corporate governance guarantees risk sharing, ethical business practices, social responsibility, and environmental goals that are aligned with Shariah philosophies. The integration of Islamic finance governance procedures with corporate, social, responsibilities (CSR), sustainable development goals (SDGs), and environ- mental, social, and governance (ESG) creates a comprehensive approach that offers sustainable financial growth. Thus, the amalgamation of Islamic finance ideologies with vigorous corporate governance procedures guarantees social and environmental development and offers the utmost sustain- able growth.